Nursing protocol in vascular trauma prevention: peripheral catheterization bundle in urgency - Paula Krempser; Cristina Arreguy-Sena; Pedro Miguel dos Santos Dinis Parreira; Anabela de Sousa Salgueiro-Oliveira
ABSTRACT Objective: to create, apply and analyze in clinical practice the effectiveness of a bundle to prevent peripheral vascular trauma to approach the peripheral venous puncture process. Method: action research with 435 adult participants in an emergency service from 2011 to 2013. Creation of the bundle for prevention of vascular trauma based on scientific evidence, ease of operation, observation and measurement with implantation through an educational intervention of the team of nursing. Effectiveness analyzed by descriptive and inferential statistics using chi-square. Consecutive sample with 95% confidence interval. Results: Five stages of the bundle were related to the catheter fixation, permanence and removal process. The incidence of vascular traumas due to vein punctures reduced by 46.41% after implantation of the bundle to prevent vascular trauma associated with emergency peripheral catheterization. Conclusion: The bundle in clinical practice reduced vascular traumas by venipuncture.